Cooperation of the School With the Family and the Local Community - Selected Aspects - Anna Błasiak; Sylwia Michalec-Jękot (Jesuit University Ignatianum in Krakow, 2024)
RESEARCH OBJECTIVE: The article describes the conditions, assumptions and benefits regarding the process of cooperation of the school with the family and the local community in the context of selected educational aspects. THE RESEARCH PROBLEM AND METHODS: The research questions were as follows: for what purpose should the school cooperate with the family and the local community, and what are the conditions for and the benefits of this cooperation? Analysis of scientific literature and analysis of existing data was used. THE PROCESS OF ARGUMENTATION: Referring to scientific studies, the key concepts for the analysis were defined descriptively and the meaning and conditions of multi‑stakeholder school cooperation were characterized in view of contemporary human needs in the context of lifelong education. RESEARCH RESULTS: The analysis shows that school is one of the most important social institutions to promote the ideas of continuous learning and the value of education. It provides education for knowledge society. The quality of education depends on the school's openness to the family and community. Building a culture of cooperation requires partnership and involvement of everyone, an activity based on dialogue, shared goals and values and mutual benefits. CONCLUSIONS, RECOMMENDATIONS AND APPLICABLE VALUE OF RESEARCH: Education is not an individual activity, but a collective endeavor, and the changes in civilization generate new challenges in this area, so multi‑stakeholder cooperation of the school, family and local community is necessary, based on the identification of resources, needs and social capital of the actors, in order to meet the intellectual and moral challenges. Educational leaders - the school principal and teachers - play a key role here.